Spritualitas Kepemimpinan Kristen Dalam Pelayanan Naposo Gereja Kristen Indonesia Klasis Parlilitan - Tulus Tumanggor; Bernhardt Siburian; Nurelni Limbong; Erman Saragih; Ibelala Gea (Journal New Light, 2024)
The purpose of this study is to determine the Importance of Naposo Leadership Spirituality in Service at GKI Sumut Parlilitan Classis. The research method in this researcher uses a qualitative research method by conducting interviews with Pastors, elders, paniroi, fathers, mothers, Naposo leaders, male youth, female youth. The data studied to examine the spiritual value of Christian leadership in the Naposo service of the Indonesian Christian Church Parlilitan Classis "The results of the study show that it is important to build spirituality for the Naposo people in order to increase close fellowship in the Naposo fellowship at the Indonesian Christian Church Parlilitan Classis". It is very important for Naposo to develop their spirituality because youth are the pillars of the church and for the future of the nation. For the Church, the Naposo people are very important, because in the future the youth will replace or lead the church, so strong spirituality is needed for Naposo. Although in today's era there are many negative influences, how young people influence it is not the other way around influenced by the times. Therefore, the spirit of Christian leadership spirituality is needed. Because spirituality is a divine power that will direct a person to do positive things.